Why Do Early-Career Adult Reconstruction Surgeons Change Jobs? An American Association of Hip and Knee Surgeons Young Arthroplasty Group Survey Study - Matan Ozery, MD; Elizabeth G. Lieberman, MD; Jenna A. Bernstein, MD; Jesse I. Wolfstadt, MD, MSc, FRCSC; David C. Landy, MD, PhD; Claudia Leonardi, PhD; Anna Cohen-Rosenblum, MD, MSc (Arthroplasty Today)
Background: There are high reported rates of burnout and job turnover among orthopedic surgeons. The purpose of this study was to investigate the prevalence of job change among early-career adult reconstruction surgeons and to examine which demographic or practice factors influenced job change. Methods: An electronic survey was distributed to all practicing surgeon members of the American Association of Hip and Knee Surgeons Young Arthroplasty Group. The survey included questions about practice type, demographics, job change, and a validated burnout questionnaire. Survey responses were collected using a secure database. Statistical analysis was performed to examine relationships between respondent characteristics and job change. Results: There were 201/389 responses (51.7%). The most common motivators for job change were better workplace culture (64%), opportunities for career growth (52%), and better alignment with values of the department/institution (45%). There were few female respondents; however, they trended toward reporting higher rates of job change (35.6% female vs 21.3% male, P = .3). Respondents who were considering changing jobs but had not done so were significantly more likely to report symptoms of burnout in all studied subscales: emotional exhaustion (P < .0001), depersonalization (P = .0002), and sense of personal accomplishment (P = .007). Conclusions: Surgeons changing jobs cited social factors such as workplace culture as reasons for leaving. Burnout symptoms were higher in surgeons considering changing jobs but improved in those who had already changed jobs. It is important to identify factors that lead to job change to guide young surgeons in job selection and improve retention.